MENINGKATKAN HASIL BELAJAR PASSING BAWAH BOLAVOLI DENGAN MODEL PEMBELAJARAN KOOPERATIF BAGI SISWA KELAS V SDN PELERET II KABUPATEN PASURUAN (STUDI PADA SISWA KELASÂ V SDN PLERET II TAHUN PELAJARAN 2011/2012) - ULUM, AMINUL (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract It has been done in the form of corrective action research learning in the fifth grade students of Pleret II Elementary School Pojentrek Pasuruan district that have difficulty in penjasorkes subjects, especially on the subject volleyball. This is shown by the low value of mastery learning students in the principal of Pleret II Elementary School district Pojentrek Pasuruan material. To improve student achievement and mastery, then do action research on Pleret II Elementary School Pojentrek Pasuruan district to implement cooperative learning model, and Pleret II Elementary School obtained the following results. Skills of teachers in the management of learning by applying the model of cooperative learning on the subject of passing UNDER showed an increase in each cycle. Activities students in learning activities demonstrate that all students can perform well and skills in every aspect has increased in each cycle. From the results of the evaluation of test scores at each cycle showed an increase in students in the classical mastery learning. Similarly, the percentage value of the class has increased. So it can be said that the students' learning achievement paing Pleret II Elementary School fifth class sub Pojentrek Pasuruan on passing the subject has increased with the implementation of the cooperative learning model. Keywords: Increasing mastery learning, pasing down, cooperative learning.